2021
DOI: 10.1186/s12888-021-03478-7
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone application for adolescents with anorexia nervosa: an initial acceptability and user experience evaluation

Abstract: Background Anorexia Nervosa (AN) is a key target for E-Health programs considering the many barriers hindering patients’ access to care and the disorder’s severity. Although these programs have become more common and effective, they often have low adherence, especially among youth. This can hinder their implementation and effectiveness in real-world settings. User experience partly overlaps with the acceptability field and may provide insight into factors affecting adherence and adoption of E-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Four studies explored participant perspectives on the use of four different smartphone applications, Recovery Record [ 46 , 50 ], TCApp [ 48 ], and a recently developed unnamed app [ 51 ]. Two studies describing the development of new smartphone applications for EDs were also identified (no data was collected) [ 40 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies explored participant perspectives on the use of four different smartphone applications, Recovery Record [ 46 , 50 ], TCApp [ 48 ], and a recently developed unnamed app [ 51 ]. Two studies describing the development of new smartphone applications for EDs were also identified (no data was collected) [ 40 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, one study examined user experience of a new smartphone app for adolescents with AN [ 51 ]. The app has an unguided self-help program based on psychoeducation, CBT, and motivational interviewing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations